Analysis of positive and negative regulatory sites and their interacting transcription factors in the zebrafish OR101-1 gene promoter - Özdemir, Metin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2018)
Each olfactory sensory neuron (OSN) of olfactory system expresses a single allele of an olfactory receptor (OR) gene from a large genomic repertoire. How an OSN selects and activates a single OR allele is not well understood yet. It was shown that epigenetic modifications are a key part of the process as well as proximal promoter region and long range cis-regulatory elements. Previous work on proximal promoter of OR101-1 gene has revealed both positive and negative regulatory sequences, deletion of which altered the expression efficiency in zebrafish embryo olfactory epithelium (OE) of transgenic vectors. It was shown that deletion of the intron from 1.2 kb upstream of OR101-1 transcription start site reduced the expression of transgenic construct, yet it was not clear whether this effect was caused by the absence of a putative O/E binding site within the intron site or by the absence of intron directly. To test this, three separate constructs were prepared. These constructs were injected in zebrafish embryos and expression efficiency was observed. While mutation of putative intronic O/E binding site resulted in 3% reduction, double mutation resulted in 7.5% reduction and swapping of intron with another resulted in 4% increase in expression, and after all, it was concluded that the expression reduction effect of intron deletion was due to the absence of the intron and not absence of the putative O/E binding site. A negative regulatory element with 562 bp length (i562) was also investigated in this study. Different length probes for each candidate site were prepared and electrophoretic mobility shift assay (EMSA) was applied to these probes with various protein sources and with anti-Zbtb7b antibody. Overall, it was seen that previously observed expression inhibition was not due to direct recognition of the candidate sites by any protein present in OE of zebrafish. The pattern of DNA-protein interaction in EMSA analyses suggests that there are cryptic sites within i562 participating in inhibitory function of the element.
Keywords: Zebra danio -- Genetics.; Olfactory receptor genes.